KIAI: FIGUR ELITE PESANTREN - Mohammad Takdir Ilahi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2014)
In a pesantren (Islamic boarding school), kiai is an strategic element. Javanese kiai mainly believe that a pesantren is a small palace where he becomes the ultimate source of power and authority. Even though he lives in a rural village, he becomes a member of elite group in social, politic and economic sides in the society. Kiai who leads big pesantren has successfully enlarged their power in term of nation so kiai could be accepted in national elite. The position of kiai is higher among all pesantren elements. The degree as an Islamic scholar is exactly a sacred degree in pesantren culture and tradition. Without his figure, it is impossible for a pesantren to develop and survive. Kiai holds an ultimate position on educate the behavior and morality of the santri (students) to be qualified and compatible Muslims generation. Kiai is not only a leader but he is also the man behind the leadership itself in supporting the progress of Islamic education institution for Muslims generations.